THE INFLUENCE OF AQUEOUS EXTRACT OF CORIANDRI (Coriandrum sativum L) FRUCTUS TO BLOOD GLUCOSE LEVEL IN GLUCOSE- PRE LOADED RATS - Agung Endro Nugroho (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2002)
Coriander contains some active compounds capable of decreasing the level of blood glucose. Moreover, aqueous extract of coriander (Coriandrum sativum L.) fruits has insulin-releasing and insulin-like activities. This research has been performed to obtain information on the effect of aqueous extract of coriander fruits on the blood glucose level in glucose-preloaded rats. The study was conducted by employing a complete random design in male Wistar rats (age 2-2,5 months, 150-250g).After the design treatments, the blood samples were collected (100-200 ul) at certain time interval. The result of each group were compared and analysed using the Mann-Whitney non-parametric method (95%). The result showed that low doses (0.014 and 0.07 % w/v) of aqueous extract of coriander fruits were unable to decrease significantly (p>0.05) the blood glucose level in glucose-preloaded glucose. On the other hand, high doses, 0.35 and 1.75 % w/v, were capable to decrease significantly (p<0.05), which are 22.11 ± 3.09 and 18.41 ± 4.88 %, respectively. Nevertheless, in the present study, the highest hypoglycaemic effect of aqueous extract of coriander fruits still lower than that of tolbutamide (p<0.05).Keywords: coriander, hypoglycaemic, glucose, tolbutamide